2013
DOI: 10.1111/cid.12191
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Frozen versus Autogenous Iliac Bone for the Rehabilitation of the Extremely Atrophic Maxilla with Onlay Grafts and Endosseous Implants: Preliminary Results of a Prospective Comparative Study

Abstract: Results of this study seem to demonstrate that FFB does not represent a reliable alternative to AB blocks because of the higher rate of bone exposure and partial loss of the grafts, the lower implant survival, and the higher peri-implant bone resorption in FFB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
1
29
1
2
Order By: Relevance
“…Chiapasco and colleagues recently demonstrated inferior peri‐implant bone stability and lower implant survival in sites received allogenous than autogenous bone block, contrary to the present results. The differences might be from caused by the different indication for the augmentation (ie, fully vs partially edentulous ridge), as the periodontal attachment on the adjacent teeth could provide volumetric stability and a source of healing.…”
Section: Discussioncontrasting
confidence: 99%
“…Chiapasco and colleagues recently demonstrated inferior peri‐implant bone stability and lower implant survival in sites received allogenous than autogenous bone block, contrary to the present results. The differences might be from caused by the different indication for the augmentation (ie, fully vs partially edentulous ridge), as the periodontal attachment on the adjacent teeth could provide volumetric stability and a source of healing.…”
Section: Discussioncontrasting
confidence: 99%
“…Techniques such as guided bone regeneration and reconstruction with autogenous bone blocks are supported by a significant bulk of literature, as demonstrated by some systematic reviews . On the other hand, the use of nonautogenous bone blocks, including allografts and xenografts, is supported by less, and often contradictory, literature with some publications reporting positive results and others reporting questionable results ().…”
Section: Classification Of Horizontal Defects According To a Prosthetmentioning
confidence: 99%
“…Nevertheless, controversial results have been reported in the literature. While some authors reported encouraging results, other studies described questionable data regarding to its resorption and long‐term sequestration of the graft …”
Section: Introductionmentioning
confidence: 99%